Design Curves for Plastic Design of Uniformly Loaded Steel Beams - Hill, Jr.; Vanderplaats, Garret N. (Engineering Journal, 1968)
Conventional methods of plastic design are relatively complex when applied to uniformly loaded beams. A curve, developed in this paper, provides a simple, quick, direct method for the design of beams subject to such uniform loads. The beams may have either constant or variable cross sections. A second curve facilitates determination of cover plate lengths.